2013
DOI: 10.1080/10242694.2013.824676
|View full text |Cite
|
Sign up to set email alerts
|

Remittances and terrorism: A global analysis

Abstract: This paper is the first global investigation of the relationship between remittances and terrorism. To discern this relationship, we draw terrorism event data from the Global Terrorism Database and International Terrorism: Attributes of Terrorism Events. When a host of standard terrorism controls is employed, lagged remittances as a share of gross domestic product have a positive and significant impact on both domestic and transnational terrorist attacks. For the venue country's viewpoint, lagged remittances h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…On the political level, the heart of this paper, international migrants are increasingly using their remittances to influence political reforms in their country of origin (O’Mahony, ). They do so by funding legitimate political parties that support democratic institutions or by funding irregular forces with the aim of replacing autocratic incumbent (Collier and Hoeffler, ; Mascarenhas and Sandler, ). Because of the sizable financial resources available to international migrants, both opposition and incumbent government compete for the support of their diaspora.…”
Section: Introductionmentioning
confidence: 99%
“…On the political level, the heart of this paper, international migrants are increasingly using their remittances to influence political reforms in their country of origin (O’Mahony, ). They do so by funding legitimate political parties that support democratic institutions or by funding irregular forces with the aim of replacing autocratic incumbent (Collier and Hoeffler, ; Mascarenhas and Sandler, ). Because of the sizable financial resources available to international migrants, both opposition and incumbent government compete for the support of their diaspora.…”
Section: Introductionmentioning
confidence: 99%
“…Third, while [45] find that remittances finance terrorism, the results of [46] relativize the role of remittances in terrorist financing in Sub-Saharan Africa. Four, we expected a negative relationship between foreign direct investment and terrorism [46] and between political stability and terrorism [47]. Five, the effect of foreign aid on terrorism is mixed.…”
Section: Source: Authormentioning
confidence: 92%
“…The first paper is by Elu and Price () who found that ‘approximately one terrorism incident is financed in sub‐Saharan Africa for remittance inflows that range between approximately one quarter of a million dollars and one million dollars’. The other paper is by Mascarenhas and Sandler () where they found that remittances have a positive impact on domestic and transnational terrorism. These two papers deserve another look for several reasons.…”
Section: Introductionmentioning
confidence: 99%